IMPACT OF COVID-19 ON THE MINING SECTOR IN KAZAKHSTAN - Kabdygaliyeva, Zere (Nazarbayev University School of Mining and Geosciences, 2022)
The COVID-19 pandemic significantly affected various industrial fields worldwide. This thesis review report will discuss the impact of the outbreak on the mining industry. Despite the cautionary and restrictive measures undertaken immediately by the mining corporations to take the situation under their control, the industry experienced losses and difficulties. The major ones concerned the well-being of employees, their employment status, maintenance of supply chains and rates of export, issues with logistics, funding and unplanned expenses. The local economies of the countries that heavily depend on mining suffered extensively due to their Gross Domestic Product values dropping significantly. The aim of this review report is to provide a thorough analysis of the impact of the COVID-19 outbreak on the above-mentioned realms of the mining industry based on the examination of the cases of Kazakhstan, India, Brazil, South America, the USA, Mongolia, African and European countries. The thesis will provide the analysis of the local Kazakhstani mining companies’ strategies to overcome COVID-19 crisis and difficulties they faced. The thorough examination of the dominant six minerals on Kazakhstan's mining market, namely aluminum, chromium, lead, coal, iron and copper, that were affected by the pandemic will be based on the analysis of the data from the official sources. The pie charts, tables, and graphs are created based on the data taken from the Bureau of national statistics of the Agency for strategic planning and reforms of the Republic of Kazakhstan. The analysis is done by evaluating the causes of deviation of prices on the ores and minerals, delays in production, exploration, transportation, and fieldworks accompanied with the strategies to resolve the occurring issues. The situation in the global mining market at the beginning of the pandemic, including the specific situation within Kazakhstan's market, is provided in detail and compared to the current one. The correlations between the flow of the COVID-19 and the drop in mining production rates are included. Based on the analysis, the forecasts about the future of the mining industry and the speed of the recovery process are covered as well.
Keywords: Type of access: Open Access